Influence of Implant Thread Morphology on Primary Stability: A Prospective Clinical Study. (5th August 2020) - Menini, Maria; Bagnasco, Francesco; Calimodio, Ivan; Di Tullio, Nicolò; Delucchi, Francesca; Baldi, Domenico; Pera, Francesco
Abstract : Objectives . The purpose of this study was to evaluate the primary stability of two implants with the same macro- and micromorphology but different thread design and analyze their clinical outcomes over a one-year period. Materials and Methods . 14 patients needing a partial rehabilitation with a delayed loading approach (DEL group: 9 patients) or a full-arch rehabilitation treated with immediately loaded fixed prostheses supported by 4 implants following the Columbus Bridge Protocol (CBP) (IL group: 5 patients) were included. In each patient, at least one SY (implant with standard threads) and one SL implant (implant with an augmented depth of the threads) were randomly inserted. Primary outcome measures were the number of threads exposed at a torque of 30 Ncm and 50 Ncm and final insertion torque. Secondary outcome measures were implant and prosthetic failure, peri-implant bone resorption, and periodontal parameters: bleeding on probing (BoP), plaque index (PI), and probing depth (PD) evaluated at 3, 6, and 12 months of healing. Results . Nineteen SY and 19 SL implants were inserted in 14 patients. Twenty implants (10 SL and 10 SY) were inserted in the IL group, while 18 (9 SL and 9 SY) were inserted in the DEL group and followed-up for 12 months. No patients dropped out. No implants and prostheses failed. No biological complications were identified. No significant differences were found between SY and SL implants comparing the number of exposed threads when inserting the implant with a torque insertion of 30 N (T student test p = .142 and U test p = .164 ). At 50 N, no threads were visible in either groups. Final torque insertion values were higher for SL (mean: 48.42 Ncm) compared to SY implants (mean: 43.42 Ncm) without a statistically significant difference. All the implants showed good clinical outcomes at the 1-year-in-function visit. Conclusions . After 12 months of function, both implant types provided good clinical outcomes without statistically significant differences between the two groups. A difference in insertion torque (even if not statistically significant) was found with higher insertion torque values for SL implants with a larger thread depth.